Targeted Cox2 gene deletion in intestinal epithelial cells decreases tumorigenesis in female, but not male, ApcMin/+ mice. Issue 2 (8th November 2013) - Cherukuri, Durga P.; Ishikawa, Tomo-o; Chun, Patrick; Catapang, Art; Elashoff, David; Grogan, Tristan R.; Bugni, James; Herschman, Harvey R.
Abstract : Mice heterozygous for mutations in the adenomatous polyposis coli gene (Apc+/− mice) develop intestinal neoplasia. Apc+/− tumor formation is thought to be dependent on cyclooxygenase 2 (COX2) expression; both pharmacologic COX2 inhibition and global Cox2 gene deletion reduce the number of intestinal tumors in Apc+/− mice. COX2 expression is reported in epithelial cells, fibroblasts, macrophages and endothelial cells of Apc+/− mouse polyps. However, the cell type(s) in which COX2 expression is required for Apc+/− tumor induction is not known. To address this question, we developed ApcMin/+ mice in which the Cox2 gene is specifically deleted either in intestinal epithelial cells or in myeloid cells. There is no significant difference in intestinal polyp number between ApcMin/+ mice with a targeted Cox2 gene deletion in myeloid cells and their control littermate ApcMin/+ mice. In contrast, ApcMin/+ mice with a targeted Cox2 deletion in intestinal epithelial cells have reduced intestinal tumorigenesis when compared to their littermate control ApcMin/+ mice. However, two gender‐specific effects are notable. First, female ApcMin/+ mice developed more intestinal tumors than male ApcMin/+ mice. Second, targeted intestinal epithelial cell Cox2 deletion decreased tumorigenesis in female, but not in male, ApcMin/+ mice. Considered in the light of pharmacologic studies and studies with global Cox2 gene knockout mice, our data suggest that (i) intrinsic COX2 expression in intestinal epithelial cells plays a gender‐specific role in tumor development in ApcMin/+ mice, and (ii) COX2 expression in cell type(s) other than intestinal epithelial cells also modulates intestinal tumorigenesis in ApcMin/+ mice, by a paracrine process. Highlights: Effect of tissue‐specific Cox2 deletion on polyposis in ApcMin/+ mice was examined. Targeted myeloid cell Cox2 deletion has no effect on polyposis in ApcMin/+ mice. Intestinal epithelial Cox2 deletion did not affect ApcMin/+ male mice polyposis. Intestinal epithelial Cox2 deletion greatly reduced ApcMin/+ female mice polyposis. In females, intestinal epithelial cell Cox2 deletion affected mainly large tumors.